Child-Adult Relationship Enhancement in Primary Care: A Randomized Trial of a Skill-Based Parent Training with Parent Mentor Adaptation. Issue 4 (May 2020) - Schilling, Samantha; Ritter, Victor; Wood, Joanne N.; Fine, Jason; Zolotor, Adam J.
ABSTRACT: Introduction: Child-Adult Relationship Enhancement in Primary Care (PriCARE) is a 6-session group training designed to teach positive parenting skills. Parent engagement in such programs is a common implementation barrier. Our objectives were to (1) examine the impact of a peer mentor on attendance and stigma and (2) replicate a previous study by measuring PriCARE's impact on child behavior and parenting practices. Method: Parents of 2- to -6-year-old children without specific behavior problems were randomized to mentored PriCARE (n = 50), PriCARE (n = 50), or control (n = 50). Stigma was measured at 10 weeks. Child behavior and parenting practices were measured at baseline and 10 weeks using the Eyberg Child Behavior Inventory (ECBI) and Parenting Scale (PS). Analysis of variance models were used to examine differences across groups. Results: There was no significant difference in attendance between mentored PriCARE and PriCARE arms (mean 3.80 vs 3.36 sessions, p = 0.35). Parents randomized to the mentor reported lower stigma (3.75 vs 5.04, p = 0.02). Decreases in the mean ECBI scores between 0 and 10 weeks were greater in the PriCARE arms (n = 100) compared with the control arm (n = 50), reflecting larger improvements in behavior [intensity: −7 (−2 to −13) vs 4 (−3 to 12) to p = 0.014; problem: −3 (−1 to −4) vs 1 (−1 to 3) to p = 0.007]. Scores on all PS subscales reflected greater improvements in parenting behaviors in PriCARE arms compared with control (all p < 0.04). Conclusion: Adapting PriCARE with a peer mentor may decrease stigma but does not improve program attendance. PriCARE shows promise in improving behavior in preschool-aged children and increasing positive parenting practices.